2013
DOI: 10.1029/2012jd018174
|View full text |Cite
|
Sign up to set email alerts
|

Nowcasting severe convective activity over southeast India using ground‐based microwave radiometer observations

Abstract: [1] In the present study, the feasibility of nowcasting convective activity is examined by using thermodynamic indices derived from the ground-based microwave radiometer (MWR) observations located at a tropical station, Gadanki (13.5 N, 79.2 E). There is a good comparison between thermodynamic parameters derived from MWR and colocated GPS radiosonde observations, indicating that MWR observations can be used to develop techniques for nowcasting severe convective activity. Using MWR observations, a nowcasting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
81
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(84 citation statements)
references
References 44 publications
2
81
0
1
Order By: Relevance
“…These timely FI data are particularly important for thunderstorm forecast in the 0 to 6 h range, as recently shown for two tropical sites (Chan, 2009;Chan and Hon, 2011;Madhulatha et al, 2013;Venkat Ratnam et al, 2013). In this paper we extend the application to two sites at midlatitude and to a few additional FIs, demonstrating the ability of MWRP retrievals to provide quality FIs similar to radiosonde, as well as the added value of continuous FI data.…”
Section: Cimini Et Al: Forecast Indices From Ground-based Microwamentioning
confidence: 91%
See 1 more Smart Citation
“…These timely FI data are particularly important for thunderstorm forecast in the 0 to 6 h range, as recently shown for two tropical sites (Chan, 2009;Chan and Hon, 2011;Madhulatha et al, 2013;Venkat Ratnam et al, 2013). In this paper we extend the application to two sites at midlatitude and to a few additional FIs, demonstrating the ability of MWRP retrievals to provide quality FIs similar to radiosonde, as well as the added value of continuous FI data.…”
Section: Cimini Et Al: Forecast Indices From Ground-based Microwamentioning
confidence: 91%
“…Note that most of the information content resides within the planetary boundary layer (Cimini et al, 2011;Löhnert and Maier, 2012) and that useful information is provided even under precipitation (Cimini et al, 2011;Xu et al, 2014). The high-temporal-resolution MWRP retrievals have recently been exploited in support of nowcasting lowlevel windshear at Hong Kong airport (Chan and Lee, 2011), dynamic weather conditions in US (Knupp et al, 2009), and intense convective weather in Hong Kong (Chan and Hon, 2011) and southeastern India (Madhulatha et al, 2013;Venkat Ratnam et al, 2013). A similar approach, though using a ground-based infrared interferometer, is also reported (Feltz and Mecikalski, 2002;Wagner et al, 2008).…”
Section: Cimini Et Al: Forecast Indices From Ground-based Microwamentioning
confidence: 99%
“…Differences between fixed volume radiometric observations and balloon-borne liquid sensor point measurements along an uncontrolled flight path contribute to the uncertainty. Example neural network liquid profile retrievals are provided by Ware et al 2003Ware et al , 2013Knupp et al 2009;Madonna et al 2011;Cimini et al 2011;Madhulatha et al 2013;Campos et al 2014;Serke et al 2014;and Gultepe et al 2015. The other method for the LWP profiling combines microwave radiometer and cloud radar measurements, but this method has 60% or larger liquid profile retrieval uncertainty (Ebell et al 2010).…”
Section: Methodsmentioning
confidence: 99%
“…The NN technique is a popular method that combines MWR observations with radiosonde climatology. Previous studies using NNs have investigated thermodynamic environments for meteorological phenomena such as bores and cold fronts (Knupp et al 2009;Spänkuch et al 2011), low-level wind shear (Chan and Lee 2011), thunderstorms (Madhulatha et al 2013), a convective cloud causing a waterspout (Raju et al 2013), and various convective storms (e.g., Chan 2009;Chan and Hon 2011). Some statistical studies on instability indices derived from NNs have shown that MWR-retrieved thermodynamic profiles have advantages in nowcasting severe storms in 0−6 h, as compared with the traditional diagnosing methods based on 12-h radiosonde observations (e.g., Ratnam et al 2013;Madhulatha et al 2013;Novakovskaia et al 2013;Cimini et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These profiles are available nearly continuously and are extensively utilized in the forecasting and analysis of intense convective weather; also they have been assimilated into numerical weather prediction models (Marzano et al, 2005;Knupp et al, 2009;Löhnert and Maier, 2012;Madhulatha et al, 2013). The instability indices calculated from the MWR-retrieved thermodynamic atmospheric profiles are also employed in operational meteorology (Chan and Hon, 2010;Cimini et al, 2015;Leena et al, 2015).…”
Section: Introductionmentioning
confidence: 99%